Comparison of LI-RADS Scores Before and After Transarterial Chemoembolization (TACE) in Hepatocellular Carcinoma Patients - Taufik Rahman; Hartono Yudi Sarastika; Widiana Ferriastuti (Transpublika Publisher, 2026)
Hepatocellular carcinoma (HCC) is the most frequent primary liver malignancy, notorious for its elevated mortality. In intermediate-stage HCC where surgical resection is contraindicated, transarterial chemoembolization (TACE) is the primary treatment modality. Accurate evaluation of therapeutic response is essential to guide ongoing patient management. The Liver Imaging Reporting and Data System (LI-RADS), particularly its Treatment Response (LI-RADS TR) criteria, provides a validated radiographic method for assessing lesions before and after locoregional interventions. This study compared LI-RADS scores before and after TACE in patients at Dr. Soetomo Regional General Hospital, Surabaya. A retrospective observational design was employed, involving 37 HCC patients who underwent TACE and abdominal CT between January 2024 and July 2025. Statistical analysis used the paired t-test or Wilcoxon test (p < 0.05). The majority of patients were male (67.6%) with a mean age of 55.3 years. Before TACE, the most common categories were LR-5 (51.4%) and LR-4 (48.6%). Following TACE, 78.4% of tumors were classified as viable and 21.6% as non-viable by LI-RADS TR. No significant difference in tumor size was observed, but tumor-to-liver ratio was significantly reduced (p < 0.001). No significant association was identified between pre-TACE LI-RADS characteristics and post-TACE LI-RADS TR categories, except for the pre-treatment tumor-to-liver ratio. TACE significantly reduced the tumor-to-liver ratio; however, most lesions remained viable by LI-RADS TR. LI-RADS and LI-RADS TR are important tools for evaluating treatment response and guiding further management in HCC patients.